Predictors of food insecurity among older adults before and during COVID-19 in the United States - Nicklett, Emily Joy; Cheng, Greta Jianjia; Morris, Zachary A. (Frontiers in Public Health, 2023)
Background The COVID-19 pandemic has strained the health and wellbeing of older adult populations through increased morbidity, mortality, and social exclusion. However, the impact of COVID-19 on the health of older adults through food security has received relatively little attention, despite the strong impact of diet quality on the health and longevity of older adults. Objective The objective of this study was to identify sociodemographic and socioeconomic predictors of self-reported food insecurity before and early in the COVID-19 pandemic among community-dwelling older adults in the United States. Methods Using longitudinal data from the Health and Retirement Study, a nationally representative sample of middle-aged and older adults in the United States, we examined the associations between sociodemographic and socioeconomic predictors of self-reported food insecurity between 2018 (N = 2,413) and June 2020 (N = 2,216) using population-weighted multivariate logistic regression models. Results The prevalence of food insecurity doubled among participants from 2018 (4.83%) to June 2020 (9.54%). In 2018, non-Hispanic Black and rural residents were more likely to report food insecurity, while individuals with higher education and greater wealth were less likely to report food insecurity in adjusted models. In June 2020, those who were relatively younger, not working due to a disability, and renting were more likely to report food insecurity. Those with an increased number of functional limitations, a recent onset of a work-limiting disability, and those who were no longer homeowners experienced an elevated longitudinal risk for food insecurity. Conclusion Future research should examine effective policies and interventions to address the disproportionate impacts of COVID-19 on populations at a heightened risk of experiencing food insecurity.